An Administrative Data-based Surrogate Definition Identifies Children Evaluated Beyond Physical Examination for Suspected Appendicitis. Issue 6 (November 2020) - Glissmeyer, Eric W.; Ryan, Sydney; Dudley, Nanette C.; Schunk, Jeff E.; Nielsen, Jeremy; Weng, Cindy; Skarda, David E.
Abstract : Introduction: Previous studies have reported on the evaluation of patients diagnosed with appendicitis. Very little is known about all patients evaluated for suspected appendicitis. Patients evaluated beyond physical examination with laboratory and imaging testing, then found not to have appendicitis, are more difficult to identify. Data readily available in administrative databases may be used to identify these patients. Methods: A multidisciplinary team developed a surrogate definition for evaluating suspected appendicitis in children based on available administrative data. Appendicitis was "suspected" if the patient underwent ultrasonography of the appendix or had a chief complaint of abdominal pain with both complete blood count performed and the word "appendicitis" in the ED provider note. Performance characteristics described the surrogate definition's ability to retrospectively identify patients evaluated for suspected appendicitis through comparison to a population identified via chart review. Results: Compared with manual chart review of 498 patients from June 2014, the surrogate definition identified patients evaluated beyond physical examination for suspected appendicitis with a sensitivity of 79.8%, a specificity of 96.3%, a positive predictive value of 83.3%, and a negative predictive value of 95.3%. Of the 94 patients evaluated beyond physical examination for suspected appendicitis, 37 (39%) underwent appendectomy. Conclusions: Health systems can retrospectively identify children evaluated beyond physical examination for appendicitis using discrete administrative data and a word search of clinical notes. This surrogate definition for evaluation of suspected appendicitis enables research in quality improvement efforts and health care resource utilization.